A Case of Clear Cell Sarcoma of Kidney in An Adult: An Extremely Rare Presentation - Vakani, Pragya Nirav; Maheshwari, Mukesh; Maheshwari, Jainil; Agarwal, Anshul; Patel, Pragnesh; Shah, Chandresh (Annals of Pathology and Laboratory Medicine, 2018)
Clear cell sarcoma of the kidney (CCSK) is a malignant renal tumor of childhood with a propensity to metastasize to bone and other organs. It is extremely rare in adults, must be differentiated from clear cell carcinoma of kidney which is more common in adults. We report a case of CCSK in a 45 year old female, confirmed by Immunohistochemistry (IHC) & managed with radical nephrectomy. The aim of this case report is to increase the awareness about this entity in adults with brief review of relevant literature.